Indigenous pathways into social research : voices of a new generation - Mertens, Donna M.; Cram, Fiona; Chilisa, Bagele (Left Coast Press, 2013)
A new generation of Indigenous researchers is taking its place in the world of social research in increasing numbers. These scholars provide new insights into communities under the research gaze and offer new ways of knowing to traditional scholarly models. They also move the research community toward more sensitive and collaborative practices. But it comes at a cost. Many in this generation have met with resistance or indifference in their journeys through the academic system and in the halls of power. They also often face ethical quandaries or even strong opposition from their own commu.